Interaction of host cellular factor ANP32B with matrix proteins of different paramyxoviruses. (3rd December 2019) - Günther, Maria; Bauer, Anja; Müller, Martin; Zaeck, Luca; Finke, Stefan
Abstract : Although most non-segmented negative-strand RNA viruses (NNSVs) replicate in the cytoplasm, NNSV proteins often exert host manipulatory functions in the nucleus. Matrix (M) proteins of henipaviruses and other paramyxoviruses shuttle through the nucleus, where host factors may bind for M modification or host-cell manipulation. Acidic leucine-rich nuclear phosphoprotein 32 family member B (ANP32B) is an interactor of Hendra and Nipah virus M. Both accumulate in the nucleus in an ANP32B-dependent manner. Here we demonstrate that the nuclear localization signal (NLS) of ANP32B is dispensable for HeV M binding. Specific purification of M-ANP32B but not of M-ANP32A complexes revealed that neither the negatively charged acidic nor the leucine-rich regions of ANP32 proteins per se mediate interactions with henipavirus M proteins. Whereas pneumovirus M did not interact with ANP32B, Newcastle disease virus (NDV, genus Avulavirus ), Sendai virus (SeV, genus Respirovirus ), Measles virus (MeV, genus Morbillivirus ) and Canine distemper virus (CDV, genus Morbillivirus ) M were able to form complexes with ANP32B. However, in contrast to NDV M and SeV M, which accumulated in the nucleus ANP32B dependently, both morbillivirus Ms did not accumulate in the nucleus, neither at ANP32B overexpression nor after nuclear protein export inhibition. These results indicate that intracellular compartmentalization of cytoplasmic morbillivirus M and nuclear ANP32B prevented an intracellular interaction. Overall, we provide evidence for a general ability of paramyxovirus M proteins to interact with ANP32B. This suggests a conserved, yet to be clarified mechanism might play a role in host manipulation and immune regulation in infected hosts.